The Application Of Hypnoparenting With The Risk Of Temper Tantrums In Preschool Children During The Covid-19 Pandemic - Ardini, Febrian Putri; Saptanto , Agus; Ratnaningrum, Kanti (Universitas Ahmad Dahlan, 2025)
Temper tantrums are a condition where children vent their uncontrolled emotions. Hypnoparenting is a therapy used by parents to control and develop children's mentality by means of hypnosis. The high number of temper tantrums in preschool-age children with a pandemic situation that has not subsided and is triggered by increased stressors in children. The purpose of this study was to find out the relationship between the application of hypnoparenting and the occurrence of temper tantrums in preschool-aged children during the Covid-19 pandemic at the Posyandu in Dorogi Village, Godong, Grobogan Quantitative research, quasi-experimental design with time series design. The sample is preschool-aged children who are at risk of temper tantrums at the Posyandu in Dorogi Village. Temper tantrum assessment was carried out using a questionnaire before and after the hypnoparenting implementation intervention. Analysis using the Wilcoxon Rank Test. There was a significant difference in the risk of temper tantrums between before and after the application of hypnoparenting (p<0.001). There is a relationship between the application of hypnoparenting and the risk of temper tantrums in preschool-aged children during the Covid-19 pandemic at the Posyandu in Dorolegi Village, Godong, Grobogan.